Pengaruh Job Satisfaction, Perception Corporate Social Responbility, Organizational Trust, Artificial Intelligence Terhadap Employee Performance Karyawan RS An-Nisa Group Tangerang - Emilisa, Netania; Istiqomah, Nur; Adiwijaya, Elang Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Job Satisfaction, Perception Corporate Social Responsibility, Organizational Trust, Artificial Intelligence on employees of An-Nisa Group Hospital Tangerang. The independent variables in this study are Job Satisfaction, Perception Corporate Social Responsibility, Organizational Trust, Artificial Intelligence and for the dependent variable in this study is Employee Performance. The method used in this research is quantitative method and the data used is primary data obtained directly from the results of distributing questionnaires and measured using a Likert Scale. This research was conducted at An-Nisa Group Hospital Tangerang with a total of 150 respondents. The data analysis technique uses SPSS. The data in this study were collected using a questionnaire and then processed using the SPSS program. The results showed that the variable Job Satisfaction (X1), Perception of Corporate Social Responsibility (X2), Artificial Intelligence (X4) had a positive influence on the variable Employee Performance (Y). While the Organizational Trust (X3) variable does not have a positive influence on the Employee Performance (Y) variable. Keywords: job satisfaction, perception corporate social responbility, organizational trust, artificial intelligence, employee performance.